2013
DOI: 10.1111/aogs.12195
|View full text |Cite
|
Sign up to set email alerts
|

Obese women's reasons for not attending a weight management service during pregnancy

Abstract: Citation: Olander, E. K. & Atkinson, L. (2013). Obese women's reasons for not attending a weight management service during pregnancy. Acta Obstetricia et Gynecologica Scandinavica, 92(10), pp. 1227Scandinavica, 92(10), pp. -1230Scandinavica, 92(10), pp. . doi: 10.1111 This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent AbstractEvaluations of services targeting obese women's gestational weight gain often report low uptake. Thus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Women's responses were complex: they expressed concerns about feeling judged or upset but, in contrast to health professional opinions, described being keen to avoid gaining excess weight; however it seemed that motivation to manage weight was often gained in retrospect: "I ate what I wanted during pregnancy and after pregnancy I was regretting it, definitely regretting it" (woman). These findings mirror those made by previous research, [19,38,39] which revealed poor perceptions of women's motivation among staff and varying levels of motivation among women themselves. Women's views in this study supported professional perceptions that weight is difficult to discuss, requires a careful and supportive approach, and that motivation is an issue.…”
Section: Women Are Not Motivatedsupporting
confidence: 88%
See 1 more Smart Citation
“…Women's responses were complex: they expressed concerns about feeling judged or upset but, in contrast to health professional opinions, described being keen to avoid gaining excess weight; however it seemed that motivation to manage weight was often gained in retrospect: "I ate what I wanted during pregnancy and after pregnancy I was regretting it, definitely regretting it" (woman). These findings mirror those made by previous research, [19,38,39] which revealed poor perceptions of women's motivation among staff and varying levels of motivation among women themselves. Women's views in this study supported professional perceptions that weight is difficult to discuss, requires a careful and supportive approach, and that motivation is an issue.…”
Section: Women Are Not Motivatedsupporting
confidence: 88%
“…Previous findings have also demonstrated a lack of information about weight management and varying levels of motivation among women during pregnancy. [19,37,39] On the other hand, without weight-related information from the health professionals who act as their key source of information and in a social environment where risks of obesity in pregnancy are not well advertised or understood, a lack of motivation in pregnancy does not seem surprising.…”
Section: Resultsmentioning
confidence: 99%
“…A considerable study strength is that we interviewed women who declined the service. There is a lack of evidence exploring why obese pregnant women decline weight management services [5,6] and research has tried and failed to recruit this hard to reach population group in the past [2].…”
Section: Discussionmentioning
confidence: 99%
“…The high costs associated with intensive interventions are known to limit reach and scalability, and to increase disparities in service provision . Further, traditional approaches with regular group or face‐to‐face health professional visits may not be convenient for many women …”
Section: Introductionmentioning
confidence: 99%